(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the artistic and philosophical interpretation of the issue of ignorance and enlightenment in the work of Yusuf Hos Hajib, a major figure in Turkish classical literature. In particular, the ideas of knowledge, reason, justice, and spiritual perfection are studied in the example of the writer’s famous work - Kutadgu bilig. The work shows ignorance as a factor that hinders the development of man and society, and enlightenment is interpreted as the main value that forms a perfect person. The research uses historical, literary, and philosophical analysis methods.